STATIC MODELING OF THE DIMENSIONAL CHAINS OF THE HOLE CENTER-FINDERS - Porokhin, Vyacheslav; Karakulev, Yuri; Minnigazimov, Ramil; Mednikov, Sergey; Zakirov, Anvar (Journal of Applied Engineering Science, 2017)
The article is devoted to estimate the center-finders accuracy for holes of large-sized case details. Methodology for analyzing center-finders accuracy using dimensional chains and computational mathematics is proposed. It is shown that the quality classes calculated for a direct task can be extended. The methodology is applied to estimate the accuracy of center-finders with typical construction using the example of the specified tolerances for the deviation from alignment in the turbine K-300-240 and the diesel engine 10D100. As a result of calculating the dimensional chain for a direct task, the following values are obtained: 5 quality class for the first case, and 6 for the second case. To check for the inverse task, a computer program that calculates the closing link by the Monte Carlo method with Gaussian distribution is written. Based on the mutual influence of the center-finder supports, tolerances can be extended to 6 and 7 respectively, without accuracy loss.
Keywords: tolerant; methodology; estimation; accuracy